Factors Related to Marital Satisfaction in Women with Major Depressive Disorder - Amiri, Shahrokh (Tehran University of Medical Sciences, 2012)
OBJECTIVE: Major depressive disorder (MDD) is one of the most common psychiatric disorders which affects married couples frequently.The present study aims to explain the role of family processes, social support and demographic factors in marital satisfaction of women with Major Depressive Disorder (MDD). METHOD: In this cross-sectional study, 188 women with MDD were randomly selected among the patients who visited Bozorgmehr Clinic of Tabriz University of Medical Sciences. The sample selection was carried out through structured psychiatric interviews based on DSM-TV-TR criteria. Data were collected using Index of Marital Satisfaction (IMS), Family Process Scale (FPS) and Norbeck Social Support Questionnaire (NSSQ).The Mann Whitney U, Multivariate and ANOVA tests were used to analyze the data. RESULTS: No relationship was observed between age, educational level, age difference of couples and number of children with family processes and marital satisfaction (p ≥ 0.05). The patients with low educational level reported less social support (p ≥ 0.05).Marital satisfaction and family coherence were lower when the husband had a psychiatric disorder (P ≤ 0.01). The family processes (family coherence, problem-solving skills, communication skills and religious beliefs) and social support positively predicted marital satisfaction, while the husband's psychiatric disorders negatively predicted marital satisfaction. CONCLUSION: The findings highlight the significance of family processes, social support and husband's psychiatric disorders in marital satisfaction of women with MDD.